2017
DOI: 10.3847/1538-4357/aa72e4
|View full text |Cite
|
Sign up to set email alerts
|

The Disk Physical Conditions of 48 Persei Constrained by Contemporaneous Hα Spectroscopy and Interferometry

Abstract: We utilize a multi-step modelling process to produce synthetic interferometric and spectroscopic observables, which are then compared to their observed counterparts. (2010) and Vieira et al. (2017). Our best-fitting combined model from Hα spectroscopy, Hα interferometry and SED fitting has a power law density fall off, n, of 2.3 and an initial density at the stellar surface of ρ 0 = 1.0 × 10 −11 g · cm −3 with a inclination constrained by Hα spectroscopy and interferometry of 45 • ± 5 • . The position angle f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Note that this value is still lower than the general expectation of about 50%. The detailed classification algorithms differ; photometric identifications of SNe Ia in SDSS (Sako et al 2011) and Pan-STARRS1 (Jones et al 2017) SN surveys show a similarly low SN Ia fraction. Figure 16; absolute magnitudes as a function of redshift are shown in Figure 17.…”
Section: Supernova Candidatesmentioning
confidence: 99%
“…Note that this value is still lower than the general expectation of about 50%. The detailed classification algorithms differ; photometric identifications of SNe Ia in SDSS (Sako et al 2011) and Pan-STARRS1 (Jones et al 2017) SN surveys show a similarly low SN Ia fraction. Figure 16; absolute magnitudes as a function of redshift are shown in Figure 17.…”
Section: Supernova Candidatesmentioning
confidence: 99%
“…" Horch et al (2020) lists it as unresolved (2015.8343) at 692 nm with detection limit ∆m of 4.72 at 200 mas, and Wang et al (2018), searching archival IUE spectra for hot sdO companions to Be stars, found no indication of such in this system. Jones et al (2017) spatially resolved the Hα emitting region using NPOI and determined that disk emission originates in a moderately large disk with a radius of 25 stellar radii, thus excluding the possibility of very close binary companions.…”
Section: ψ Permentioning
confidence: 99%
“…LBOI has been extremely successful in the direct resolution of Be stars disks, with many examples provided by interferometers such as the Mark III Stellar Interferometer (Quirrenbach et al 1994, ζ Tau) and the Navy Precision Optical Interferometer (NPOI; Tycner et al 2003Tycner et al , 2004Tycner et al , 2005Tycner et al , 2006Tycner et al , 2008Sigut et al 2015;Jones et al 2017, including o Aqr, γ Cas, β CMi, χ Oph, 48 Per, φ Per, η Tau, and ζ Tau). These studies utilized measurements obtained simultaneously in many spectral channels covering a wide spectral range where the source is unresolved, or weakly resolved (the continuum emission from the photosphere of the central star) to calibrate the data in one or two spectral channels containing a strong signal in the Hα line originating in the optically thick circumstellar envelope that is clearly resolved in nearer sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carciofi (2011) used the VDD model to construct the basis of new paradigm for the interpretation of Be stars observations. Then, it was widely used to successfully model Be stars Silaj et al, 2010;Touhami et al, 2011;Carciofi et al, 2012;Klement et al, 2015;Vieira et al, 2015;Faes et al, 2016;Arcos et al, 2017;Jones et al, 2017;Klement et al, 2017;Vieira et al, 2017;Marr et al, 2018;Rímulo et al, 2018). More details about the VDD model can be found in Sect.…”
Section: The Disks Of Be Starsmentioning
confidence: 99%